Stress and eating disorder behavior in anorexia nervosa as a function of menstrual cycle status. Issue 2 (12th November 2013) - Jappe, Leah M.; Cao, Li; Crosby, Ross D.; Crow, Scott J.; Peterson, Carol B.; Le, Daniel; Engel, Scott G.; Wonderlich, Stephen A.
ABSTRACT Objective Fluctuations in ovarian hormones during the menstrual cycle and psychosocial stress contribute to eating disorder (ED) behavior. Method Using ecological momentary assessment techniques, this study examined relationships between stress and binge eating, self‐induced vomiting, and dietary restriction based on menstrual cycle status in anorexia nervosa (AN). One hundred nine females with full and subthreshold AN (17–45 years old) recorded ED behavior and stress ratings over 2 weeks. Using hierarchical linear modeling, individuals with eumenorrhea and those with amenorrhea or oligomenorrhea were compared. Results Following episodes of meal skipping, momentary stress decreased in individuals with normal menstrual cycles and increased in those with irregular menstrual cycles. Discussion Results suggest that changes in stress severity in response to food restriction may differ based on ovarian hormonal status and may be a mechanism by which AN is maintained in individuals without menstrual disturbance. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:181–188)